Hypomimia in Parkinson's Disease: What Is It Telling Us? - Maycas-Cepeda, Teresa; López-Ruiz, Pedro; Feliz-Feliz, Cici; Gómez-Vicente, Lidia; García-Cobos, Rocío; Arroyo, Rafael; García-Ruiz, Pedro J. (Frontiers in Neurology, 2021)
Introduction: Amimia is one of the most typical features of Parkinson´s disease (PD). However, its significance and correlation with motor and non-motor symptoms is unknown. The aim of this study was to evaluate the association between amimia and motor and non-motor symptoms including cognitive status, depression and quality of life in PD patients. We also tested the blink rate as a potential tool for measuring objectively upper facial bradykinesia. Methods: We prospectively studied amimia in PD patients. Clinical evaluation was performed using the Unified Parkinson´s Disease Rating Scale (UPDRS) and timed tests. Cognitive status, depression and quality of life were assessed using the Parkinson´s Disease cognitive Rating scale (PD- CRS), the 16-Item Quick Inventory of Depressive Symptomatology (QIDS-SR16) and the PDQ-39, respectively. Amimia was clinically evaluated according to item 19 of UPDRS III. Finally, we studied upper facial amimia by measuring resting blink frequency and blink rate during spontaneous conversation. Results: We included 75 patients. Amimia (item 19 UPDRS III) correlated with motor and total UPDRS (r: 0.529 and 0.551 Spearman), and its rigidity, distal bradykinesia and motor axial sub-scores (r:0.472; r:0.252 and r:0.508 respectively); Hoehn and Yahr scale (r: 0.392), timed tests, gait freezing, cognitive status (r: 0.29) and quality of life (r: 0.268) correlated with amimia. Blinking frequency correlated with amimia (measured with item 19 UPDRS), motor and total UPDRS. Conclusion: Amimia correlates with motor (especially axial symptoms) and cognitive situation in PD. Amimia could be a useful global marker of overall disease severity, including cognitive decline